Knowledge engineering and semantic web : 8th International Conference, KESW 2017, Szczecin, Poland, November 8-10, 2017, Proceedings /: 8th International Conference, KESW 2017, Szczecin, Poland, November 8-10, 2017, Proceedings. (2017) - Unknown
No abstract available